Indirect detector for ultra-high-speed X-ray micro-imaging with increased sensitivity to near-ultraviolet scintillator emission - Lukić, Bratislav; Rack, Alexander; Helfen, Lukas; Foster, Daniel J.; Ershov, Alexey; Welß, Richard; François, Stéphane; Rochet, Xavier (Journal of Synchrotron Radiation, 2024)
Ultra-high-speed synchrotron-based hard X-ray (i.e. above 10 keV) imaging is gaining a growing interest in a number of scientific domains for tracking non-repeatable dynamic phenomena at spatio-temporal microscales. This work describes an optimized indirect X-ray imaging microscope designed to achieve high performance at micrometre pixel size and megahertz acquisition speed. The entire detector optical arrangement has an improved sensitivity within the near-ultraviolet (NUV) part of the emitted spectrum (i.e. 310-430 nm wavelength). When combined with a single-crystal fast-decay scintillator, such as LYSO:Ce (Lu2-xYxSiO5:Ce), it exploits the potential of the NUV light-emitting scintillators. The indirect arrangement of the detector makes it suitable for high-dose applications that require high-energy illumination. This allows for synchrotron single-bunch hard X-ray imaging to be performed with improved true spatial resolution, as herein exemplified through pulsed wire explosion and superheated near-nozzle gasoline injection experiments at a pixel size of 3.2 μm, acquisition rates up to 1.4 MHz and effective exposure time down to 60 ps.
CRIS-Team Scopus Importer:2024-09-13
Keywords: high-speed imaging; indirect X-ray detectors; micro-imaging; polychromatic radiation